Social media techniques and their impact on the performance of luxury goods market - Tuarez Menéndez, Katiuska Alexandra; Mejía Vásquez, Pericles; Molina Quiroz, Claudia Analia (Ingeniería Solidaria, 2025)
Introduction: This article is the product of a master’s research project; in the current context, the presence of digital techniques is crucial for the success of local companies such as Isa Joyas in Montecristi, which faces the challenge of integrating traditional practices with digital strategies. The study was carried out at the Universidad Laica Eloy Alfaro de Manabí in Manta in 2025. Problem: The research focuses on how social media actions can enhance customer recognition and acquisi-tion, as well as improve brand perception in an increasingly digital environment. Objective: The main objective is to analyze the impact of social media strategies on Isa Joyas’ commercial performance, evaluating their effectiveness in customer loyalty and brand growth. Methodology: A quantitative approach with a descriptive design was used, administering surveys to a non-pro-bability sample of 50 women aged 20 to 45. A Likert-type scale was employed, and the instrument was valida-ted using Cronbach’s alpha coefficient. Results: The findings indicate a positive correlation between social media actions and company performance, highlighting the importance of digital content in building trust and strong relationships with customers. Conclusion: Social media strategies are fundamental to the success of Isa Joyas, improving its visibility and fostering customer loyalty. Originality: This study provides a detailed perspective on the impact of social media on a local business, contri-buting to the literature on digital marketing in the artisan sector. Limitations: Limitations include the small sample size and the lack of longitudinal analysis, suggesting the need for more extensive future research.